Cloning of synthetic gene including antigens against Urinary Tract Infections in pET28a+ vector - Zohreh Haghri; Jamil Kheirvari Khezerloo; Masoum Amraee; Afsaneh Yavari (Islamic Azad University, 2017)
There are many different bacterial infections in the world that patients are suffering from and research teams are trying to find suitable ways to prevent and treat them. Urinary Tract Infections (UTIs) are most important infections in the world , and they are more common among women because vaginal cavity is near to urethral opening. The aim of this study is cloning of synthetic gene include antigens against UTIs in pET28a+ vector. Antibiotic resistant has been increasing because of antibiotic overuse recently, so It shows the necessity of developing a vaccine against these infections. There for, it will be imperative to develop a vaccine instead of antibiotics. This infection causes by many organisms, most important of which are Uropathogenic Escherichia coli (UPEC), Proteus mirabilis and Klebsiella pneumoniae Uropathogenic Escherichia .coli is the most important microorganism that causes these infections more than other bacteria, so in developing a vaccine it is the most important one, that have to be considered. The synthetic Gene which was designed against these three bacteria including antigens which are important and common to cause these infections. This gene has involved 1293bp. It was ordered to Gene Ray Biotechnology. Primers were designed by Gene Runner. Gene and pET28a+ vector was checked by SnappGene. Synthetic gene was multiplied by PCR and cloned in pET28a+ vector. Construct was transformed into E. coli TOP10.The clone was confirmed by PCR, Digestion. This data indicates that this gene can be expressed and it might be a vaccine candidate to protect people from these infections in the future.